Вплив гетерогенності тетраплоїдного запилювача на прояв господарсько-цінних ознак ЧС гібридів цукрових буряків - Корнєєва, М.О.; Мацук, М.Б.; Чемерис, Л.М. (Фактори експериментальної еволюції організмів, 2015)
Aims. In triploid CMS sugar beet hybrids, for heterosis by agronomic signs to occur, it is necessary to involve a tetraploid
population of pollinators in crossing stable by their ploidy level. However, in practical breeding one can come across
triploid forms among tetraploid plants, which may lead to the formation of aneuploidies in F1 affecting the expression
of agronomic traits in hybrids. Methods. By the top cross method, crossed were CMS lines originated from Ivanivska
EBS, Uladivka EBS and tetraploid pollinator populations differed by part of triploid plants, namely 12.5, 25 and 50 %.
We determined the agronomic performance in CMS hybrids of sugar beet by conventional methods. Results. With a share
of triploid plants in a population of tetraploid component increasing, increased a share of aneuploidies (up to 37.5 %)
infl uencing agronomic traits. In hybrid 1316/1043, germination reduced from 92 to 74 %, in hybrid 1363/1043 from 89 to
73 %. Performance in hybrids involving CMS forms originated from Ivanivska EBS and Uladivka EBS also decreased,
respectively, from 117–129 to 98–104 % (as compared to standard). Conclusions. High degree of heterogeneity of
tetraploid pollinators according to their ploidy level infl uences agronomic characteristics due to the increased number
of aneuploidies in CMS hybrids of sugar beet. Having used stabilized tetraploid populations as a parent component we
obtain the highest performance; triploids share of 25 % signifi cantly lowers seed germination and performance.
Keywords: sugar beet, hybrid, pollinator, heterogeneity, CMS line, germination, productivity performance.